(Hyper) ghettos latinos. Theoretical approach to the phenomenon of marginality in latin american cities - Labbé Céspedes, Gricel (2021)
Public and academic discourse in Latin America frequently refers to the areas of material misery as «ghettos», quantitatively delimiting and stripping away the sociological and historical value that presides over these territories. In this sense, the research through a content analysis revisited and resorted to the theoretical proposal of urban poverty of the sociologist Loic Wacquant in order to; 1) enrich the discussion on the phenomena of deterioration, obsolescence and marginality, and 2) identify the relevance of talking about the ghetto in the Latin American reality. The theoretical work managed to show the existence of two historically constructed socio-spatial forms, the community ghetto and the hyperghetto. Both cannot be conceived only as areas that concentrate urban poverty and social pathologies, on the contrary, they are perpetuated ideological spaces, through the (in) actions of certain institutions that may or may not be available in the territories. Faced with such discourse, it was corroborated that in the Latin American reality it is possible to speak both of a transmutation from ghettos to hyperghettos, and of spaces that were born and have been perpetuated as hyperghettos.